Pengembangan Kemampuan Motorik Halus Melalui Kegiatan Meremas - Desi Anggraini; Desri Wahyuni; Elfarini Susanti (Jurnal Pendidikan Tuntas, 2023)
This research is motivated by the low fine motor skills of Group B children at TK Pernata Bunda in Harau Village. One solution to address this issue is to implement pipette folding activities. This study aims to improve fine motor skills in Group B at TK Pernata Bunda in Harau Village. The research method used in this study is Classroom Action Research (CAR). This classroom action research was conducted in two cycles, with two meetings in each cycle. Data collection techniques used were observation and documentation. The results of this research show an improvement in children's scores from the pre-action phase, Cycle I, to Cycle II, which can be described as follows: In the pre-action phase, 7 children or 63.64% had low scores (BB), then in Cycle 1, this decreased to 3 children or 27.27%, and in Cycle II, it became 0 children or 0%. The moderate score (MB) in the pre-action phase was 2 children or 18.18%, then in Cycle 1, it became 2 children or 18.18%, and in Cycle II, it became 0 children or 0%. The high score (BSH) in the pre- action phase was 1 child or 9.09%, then in Cycle 1, it became 3 children or 27.27%, and it remained at 3 children or 27.27% in Cycle II. The very high score (BSB) in the pre-action phase was 1 child or 9.09%, then in Cycle 1, it became 3 children or 27.27%, and in the end, in Cycle II, it increased to 8 children or 72.73%. Based on the above research results, the researcher recommends that teachers consider squeezing grass jelly activities as an alternative method to enhance children's fine motor skills. Keywords: Fine motor skills, squeezing grass jelly activities, classroom action research